The Challenges of Local Authority in Malaysia in Assessment Rate Arrears Collection - Mohd, Elina; Ayub, Zainal Amin; Mohd Anuar, Haslinda (Global Academic Excellence, 2018)
Assessment rates are one of the major revenues for the local authority in Malaysia. Assessment rates are collected by local authorities for the provision of services to the residents. However, low assessment rates collection but high assessment rates arrears become an issue among local authorities in Malaysia. This issue of rates arrears is a major issue that is getting serious every year and hard to solve. It stems from a variety of factors including legislation on local authorities), management and the administration of local authorities. This study aims to examine the factors of assessment rate arrears and to suggest and recommend how to overcome those obstacles. The scope of the study, however, is limited to the local authorities in the northern region of Malaysia only. The study employs sociolegal research where apart from library-based research, data is collected through interviews with Mayor or Council’s President, and senior officers from local councils in Penang, Kedah, and Perlis. The analysis of the data is conducted by using descriptive analysis. This study finds that there are four aspects that contribute to the high assessment rates arrears which are enforcement, legal, administration and management and economic. Thus, a few recommendations were proposed to local authorities in designing better approach in servicing the public as well as overcoming the highlighted issues